PENGENTASAN KEMISKINAN YANG KOMPREHENSIF DI BAGIAN WILAYAH TERLUAR INDONESIA - KASUS KABUPATEN NUNUKAN, PROVINSI KALIMANTAN UTARA (Comprehensive Poverty Reduction in Indonesian Outermost Regions - Case Study of Nunukan Regency-North Kalimantan Province) - Sri Rum Giyarsih (Pusat Studi Lingkungan Hidup Universitas Gadjah Mada, 2014)
ABSTRAKKabupaten Nunukan terletak di Provinsi Kalimantan Utara yang merupakan salah satu kabupaten terluar di Indonesia. Kondisi pemilikan aset sumberdaya yang bervariasi antar kecamatan di Kabupaten Nunukan menyebabkan variasi kondisi kemiskinan di wilayah ini. Penelitian ini bertujuan untuk mengetahui kondisi kemiskinan di Kabupaten Nunukan dan merumuskan program pengentasan kemiskinan yang komprehensif di Kabupaten Nunukan. Metode yang digunakan dalam penelitian ini adalah metode survai dengan pengumpulan data berupa observasi lapangan, wawancara mendalam, dan diskusi kelompok terfokus. Pengolahan dan analisis data dilakukan secara deskriptif kualitatif. Hasil penelitian menunjukkan bahwa kondisi kemiskinan di Kabupaten Nunukan bervariasi antar kecamatan. Kondisi ini disebabkan oleh bervariasinya pemilikan aset sumberdaya antar kecamatan. Penelitian ini juga menemukan bahwa terdapat dua pola pengentasan kemiskinan yang komprehensif di Kabupaten Nunukan. Pola pengentasan kemiskinan yang dimaksud adalah pola pengentasan kemskinan untuk kelompok anak-anak berupa pendidikan ekstra kurikuler ekonomi kreatif produktif dan pola pengentasan kemiskinan untuk kelompok dewasa adalah program pelatihan, bantuan modal, pendampingan, monitoring, dan pemasaran hasil melalui wadah Usaha Mikro, Kecil, dan Menengah (UMKM). ABSTRACTNunukan Regency, located in the North Borneo Province, is one of Indonesia's outer regions. The variation of resources ownership among districts inside Nunukan Regency causing different poverty level in this region. This study aims to determine the poverty condition in Nunukan Regency and to formulate a comprehensive poverty reduction program in this regency. The method used in this study is based on survey method, consists of data collection from field observations, in-depth interviews, and focus group discussions. Data processing and analysis were analyzed using descriptive-qualitative analysis. The results showed that there was a variation of poverty conditions for each district in Nunukan Regency. This condition was caused by the variation of resource ownership among the districts. This study also reveal that there were two patterns of comprehensive poverty reduction in Nunukan Regency. The patterns of poverty reduction consist of the reduction for groups of children by conducting extra-curricular education and creative economy productive program, while poverty reduction for adult groups consists of training programs, financial aids, mentoring, monitoring, and products marketing through micro, small, and medium scale corporation. value of water, the community is expected to support the preservation of MKPSF ecosystems. Economic value of water was aproached by estimating the willingness to pay (WTP) of community in two villages directly adjacent to MKPSF. Respondents are the people of the two villages which are the source of water comes from MKPSF. Respondents' willingness to pay values obtained from interviews using open-ended questions. The results showed that the total economic value of water MKPSF region derived from the value of water for household and water for transportation was Rp. 888,834,365,275.25 per year or Rp. 6,431,507.71 per hectare per year. This suggests that in relation to the availability of water for surrounding communities, MKPSF provide significant benefits that can be monetary assessed. So that the sustainability of MKPSF ecosystem should be supported to maintain environmental quality and economic sustainability.